Blockchain-Based Service Oriented Privacy-Preserving Data Sharing over Distributed Data Streams in Asynchronous Environment - P., Suganthi; A., Malini; Lilian J., Felicia; Vetriveeran, Divya (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Innovative city applications use information and communication technologies to function various operations efficiently. The widespread use of the Internet of Things (IoT) can be viewed in several applications like smart cars, smart cities, e-commerce, and cyber-physical systems. The huge amount of data produced and transmitted by these systems is handled by cloud-based storage services, which are vulnerable to multiple threats risking the privacy and security features of the application. Cloud storage services employ encryption algorithms to ensure data confidentiality, but it fails to address the privacy issues. Apart from the privacy risks, in these systems, the identity of a user who shares and accesses the data is traceable, as it is required to verify user eligibility before providing access. Also, a vast amount of daily data is stored on a centralized system that processes service requests from multiple users, posing considerable risks to the system’s stability during peak periods. To address these challenges faced during the data sharing process in a centralized system, Service Oriented Privacy-Preserving Data Sharing (SOPPDS) platform based on a blockchain framework is proposed. The modified Key Policy-Attribute-based Encryption (MKP-ABE) technique is applied to securely share the data between the service owners and the service consumers. It was evident from the performance evaluation of the proposed SOPPDS platform that the encryption process takes lesser time than the decryption process. Also, the cryptographic operations performed on the prime order sets exhibited increased latency and computational cost. It was observed that comparatively, cryptographic operations performed on composite order sets could overcome the issues in prime order sets. SOPPDS platform works well in preserving the users’ privacy, ensuring anonymity in the data sharing process, and maintaining the confidentiality of the data shared in the system